Toward Precision Deposition of Conductive Charge‐Transfer Complex Crystals Using Nanoelectrochemistry. Issue 4 (1st March 2023) - Kilani, Mohamed; Ahmed, Mostak; Mayyas, Mohannad; Wang, Yifang; Kalantar‐Zadeh, Kourosh; Mao, Guangzhao
Abstract: The lack of understanding for precise synthesis and assembly of nano‐entities remains a major challenge for nanofabrication. Electrocrystallization of a charge‐transfer complex (CTC), tetrathiafulvalene bromide (TTF)Br, is studied on micro/nanoelectrodes for precision deposition of functional materials. The study reveals new insights into the entire CTC electrocrystallization process from the initial nanocluster nucleation to the final elongated crystals with hollow ends grown from the working electrode to the neighboring receiving electrode. On microelectrodes, the number of nucleation sites is reduced to one by lowering the applied overpotential or precursor concentration. Certain current–time transients exhibit significant induction periods prior to stable nucleus growth. The induction regime contains small fluctuating current spikes consistent with stochastic formation of precritical nanoclusters with lifetimes of 0.1–30 s and sizes of 20–160 nm. Electrochemical analyses further reveal rate, size distribution, and formation/dissipation dynamics of the nanoclusters. Crystal growth of (TTF)Br is further studied on triangular nanoelectrode patterns with thickness of 5–500 nm, which shows a mass‐transfer‐controlled process applicable for precision deposition of functional (TTF)Br crystals. This study, for the first time, establishes CTC nanoelectrochemistry as a platform technology for precise deposition of conductive crystal assemblies spanning the source and drain electrode for sensing applications. Abstract : The electrocrystallization of a charge‐transfer complex is studied on micro/nanoelectrodes, from the earliest stage of nanocluster nucleation to the final crystal grown purposefully across neighboring electrodes, by varying key control parameters: applied potential, precursor concentration, and electrode geometry. This work provides fundamental understanding of controlled nucleation and crystal growth underpinning future scale up of charge‐transfer complex nanoelectrochemistry.